Rancang Bangun Sistem Informasi Pelayanan Medis Pada Klinik Dr. Afriyanti Menggunakan Model Waterfall - Eva Rahmawati; Hylenarti Hertyana; Elly Mufida; Ria Ria (Universitas Bina Sarana Informatika, 2020)
Service process, it is necessary to handle and process the relevant data well. Dr. Clinic Afriyanti is a health unit that provides public health services to the community. In the health services provided at the Dr. Afriyanti is currently still conventional which includes writing and storing patient data still using paper media. And there are no important reports required for the clinic. From these conditions can hamper the time when searching for patient data, and also can lead to errors in writing. Besides, the stored data is vulnerable to unpredictable data loss and damage. To overcome the problems that exist in the previous system, we need a computer-based information system. With this program, it will be easier to find patient data, patient data is stored more safely and can make reports easily and with accurate results. This research uses UML as a tool and PHP as a programming language in the design of medical service information systems.